Prediksi Penjualan Restoran Go Chicken Karawang Menggunakan Metode Linear Regresi - Alya Mutiara Dewi; Fatimah Nasywa Azhar; Chaerur Rozikin (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to predict the sales of Go Chicken Karawang restaurant using linear regression method. Daily restaurant sales data during a certain period were collected and analyzed. Subsequently, a linear regression model was developed to predict sales based on the daily data of Go Chicken Karawang restaurant. The study used the Waikato Environment of Knowledge Analysis (WEKA) machine learning. The analysis results showed that the linear regression model was able to predict restaurant sales with the desired level of accuracy. This research can assist restaurant management in production planning, inventory, and marketing strategies.